Dosimetric evaluation of cobalt-60 teletherapy in advanced radiation oncology. Issue 1 (26th October 2018) - Mathuthu, Manny; Mdziniso, Nhlakanipho Wisdom; Asres, Yihunie Hibstie
Abstract: Background: Recent investigations demonstrate a strong potential for cobalt-60 (Co-60)-based teletherapy. The influence of the lower energy and penetration of a cobalt-60 beam compared with linear accelerator beams is negligible for intensity-modulated radiotherapy. Purpose: The aim of this research is to investigate source head fluence modulation in cobalt-60 teletherapy by using a three-dimensional (3D) physical compensator and secondary collimator jaw motion. Materials and methods: The Oncentra treatment planning system was used to develop three hypothetical plans by secondary collimator jaw motion. A clinical MDS Nordion Equinox 80 cobalt-60 teletherapy unit was used to acquire conventional water phantom beam characteristics. Fluence modulation experiments were executed at 5·0 cm depth in a PTW universal intensity-modulated radiation therapy (IMRT) verification phantom using calibrated Gafchromic external beam therapy 2 (EBT2) and RTQA2-1010 film batches. Gafchromic EBT2 film was used to sample intensity maps generated by secondary collimator jaw motion, yet Gafchromic RTQA2-1010 film sampled maps from the 3D physical compensator. The solid-state drives used were 75·0 and 74·3 cm for the Gafchromic EBT2 and Gafchromic RTQA2-1010 film measurements. Results: A 2D gamma index analysis was coded to compare EBT2 film measurements with Digital Imaging and Communications in Medicine data. This analysis was also used to verify film measurements versus Monte-Carlo simulations. Conclusion: Lateral beam profiles generated from water phantom measurements were used to establish source head fluence modulation on the film measurements. The source head fluence of a cobalt-60 teletherapy beam could be modulated by secondary collimator jaw motion and using a 3D physical compensator.